An 8‐Year‐Long Low‐Frequency Earthquake Catalog for Southern Cascadia. Issue 4 (18th April 2022) - Ducellier, Ariane; Creager, Kenneth C.
Abstract: Low‐frequency earthquakes (LFEs) are small magnitude earthquakes with typical magnitude less than 2 and reduced amplitudes at frequencies greater than 10 Hz relative to ordinary small earthquakes. Their occurrence is often associated with tectonic tremor and slow‐slip events along the plate boundary in subduction zones and occasionally transform fault zones. They are usually grouped into families with all the earthquakes of a given family originating from the same small patch on the plate interface and recurring more or less episodically in a bursty manner. In this study, we extend the LFE catalog obtained by Plourde et al. (2015), https://doi.org/10.1002/2015gl064363 during an episode of high tremor activity in April 2008 to the 8‐year period 2004–2011. All of the tremors in the Boyarko et al. (2015), https://doi.org/10.1016/j.epsl.2015.06.026 catalog south of 42° North have associated LFE activity, but we have identified several smaller episodes of LFEs without associated tremor activity, and extend their catalog forward and backward by a total of about 3 years. As in northern Cascadia, the downdip LFE families have recurrence intervals several times smaller than the updip families. For the April 2008 Episodic Tremor and Slip event, the best recorded LFE families exhibit a strong tidal Coulomb stress sensitivity starting 1.5 days after the rupture front passes by each LFE family. The southernmost LFE family, which has been interpreted to be on the subduction plate boundary, near the updip limit of tremor, has a very short recurrence time. Also, these LFEs tend to occur during times when predicted tidal Coulomb stress is discouraging slip on the plate boundary. Both observations suggest that this LFE family may be on a different fault. Plain Language Summary: Low‐frequency earthquakes (LFEs) are small‐magnitude earthquakes with typical magnitude less than 2 and reduced amplitudes at frequencies greater than 10 Hz relative to ordinary small earthquakes. They are usually grouped into families with all the earthquakes of a given family originating from the same small patch on the plate interface. LFEs tend to happen in bursts with dozen of earthquakes occurring within a few days, followed by weeks or months of quiet. In this study, we extend the LFE catalog obtained by Plourde et al. (2015), https://doi.org/10.1002/2015gl064363 to the 8‐year period 2004–2011. As in northern Cascadia, the LFE families located at a greater depth (downdip) are more active, with shorter time intervals between two earthquake bursts, than the LFE families located at a shallower depth (updip). Earth tides also have an influence on LFE activity: LFEs are more likely to occur when the stress changes associated with the tides favor shear failure on the plate boundary. Key Points: We establish an 8‐year‐long low‐frequency earthquake (LFE) catalog for southern Cascadia Families from the subduction zone are mainly active during the big tremor events with downdip families more active than updip families LFE activity is sensitive to tidal stress changes